Learning strategy used by high, mid and low achievers of english to develop reading skill: a case study at muhammadiyah university of surakarta - Khasanah, Nur; , Prof. Dr. Endang Fauziati, M. Hum; , Dr.Dwi Haryanti, M.Hum (2014)
The aims of this research are to analyze learning strategies used by high, middle and low achiever students in reading to develop reading skill. The subjects of this case study are students who have high, mid and low achiever in reading subject. There are two sources of data namely event and informants. Methods of collecting data are observation and interview. Methods of analyzing data are data reduction, data display and conclusion drawing/verification. And the object is focused on the learning strategies used by students to develop reading skill. There are three results, they are: 1) The learning strategies used by high achiever student to develop vocabulary skill are 7 meta-cognitive and 10 cognitive strategies. Then, the learning strategies used by mid achiever student to increase vocabulary skill are 4 meta-cognitive, 7 cognitive, and 2 socio-affective strategies. And the learning strategies used by low achiever student to enrich vocabulary skill are 4 meta-cognitive, 4 cognitive, and 1 socio-affective strategy. 2) The learning strategies used by high achiever student to develop pronunciation skill are 6 metacognitive and 7 cognitive strategies. Then, the learning strategies used by mid achiever student to advance pronunciation skill are 4 meta-cognitive, 4 cognitive and, 2 socio-affective strategies. And the learning strategies used by low achiever student to arise pronunciation skill are 3 meta-cognitive, 4 cognitive, and 1 socioaffective strategy. 3) The learning strategies used by high achiever student to develop understanding implicit information are 6 meta-cognitive and 6 cognitive strategies. Then, the learning strategies used by mid achiever student to develop understanding implicit information are 3 meta-cognitive, 3 cognitive, and 2 socioaffective strategies. And the learning strategies used by low achiever student to develop understanding implicit information are 3 meta-cognitive, 2 cognitive, and 1 socio-affective strategy.